Development of the Religious Character of the Nation through Learning Religious Songs: Teachers’ Perception and Challenges - Julia, J.; Supriyadi, Tedi; Iswara, Prana Dwija (Harmonia: Journal of Arts Research and Education, 2022)
Songs as learning media provide an aesthetic experience for students and can also teach character. Academics in many countries pay little attention to this issue because songs are mostly used to memorize foreign language vocabulary. This study investigates teachers’ perceptions of using songs to build students’ character. This study focuses on exploring teachers’ perceptions of the development of religious character as a core character in the curriculum in Indonesia through songs. The case study design was employed by involving 45 elementary school teachers spread over several districts in West Java province. This research was carried out in several stages; First, by preparing questionnaires distributed online; Second, by following up the answers to the questionnaire by conducting in-depth interviews; Third, by analyzing the data in an inductive-thematic manner in relation to learning problems, psychological and social issues arose. The research resulted in themes related to teachers’ perceptions of developing students’ religious character through religious songs. Four themes were explored in-depth related to teacher appreciation for songs, the benefits of religious songs, teacher challenges, and instructional design. It can be drawn that the song function was not only limited to developing a cognitive domain that functioned to remember and collect facts and data but could also be a means of developing students’ characters, especially religious characters. From the teacher’s perspective, religious songs were able to develop students’ religiosity dimension, including students’ beliefs, worship, appreciation, knowledge, and morals. Hence, this study contributes to the importance of developing songs related to religious themes to develop national character.